Combining the Concept of Plane Figures in the Game of Engklek through a Motion-Based Ethnomathematics Approach - Mahardika Darmawan Kusuma Wardana; Mochamad Nashrullah; Mochamad Alim Ahaddin (International Journal on Integrated Education, 2026)
Learning about flat shapes in elementary school is often conveyed thru images, definitions, and formulas that are not yet fully connected to the real experiences of the students. The game of hopscotch offers a cultural context as well as a concrete learning space because its playing pattern is composed of various geometric shapes and is played thru physical activity. This article aims to explain how the concept of flat shapes can be integrated with the game of hopscotch thru ethnomathematics, game-based learning, and movement-based learning approaches. The article is composed using a conceptual review of selected studies with DOIs that are available online. The synthesis results show that the hopscotch squares can be used to introduce squares, rectangles, triangles, semicircles, symmetry, congruence, perimeter, area, and composite shapes. Activities such as throwing the gaco, jumping, measuring squares, comparing shapes, and explaining game strategies allow students to connect visual representations, body movements, language, and mathematical symbols. This integration not only concretizes geometric concepts but also strengthens mathematical communication, collaboration, sportsmanship, and appreciation for local culture. Thus, the game of engklek can be developed into a contextual, active, and meaningful flat geometry learning environment, both in the form of direct play and interactive digital media.